Peran komunitas army bts terhadap kesehatan mental remaja ? - Yuriadi, Yuriadi; Lestari, Bawinda Sri; Suharyuni, Nur Hosna Widya (SUKMA : Jurnal Penelitian Psikologi, 2024)
Abstract Mental health problems in today's life often occur among teenagers, ranging from stress, and depression to frustration in facing various physical trials, demands, and challenges. This study aims to determine the role, impact, and whether Army BTS can solve life's problems. The method used in this study was qualitative with three respondents, data collection was carried out using interviews and observation. The results of this study state that the Army BTS community can be used as a way to voice everything in the form of self-love and provide motivation. The impact of community is on one's mental health, knowing how to deal with one's condition, having friends to share stories with, and helping you get back on your feet. Keywords: community, BTS Army, mental health, teenagers.